2007
DOI: 10.1177/0193945906293793
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Behavioral Program to Prevent Incontinence

Abstract: This exploratory study assesses factors predicting adherence to a behavioral intervention to prevent urinary incontinence. Community-dwelling, post-menopausal women (N = 164) were taught pelvic floor muscle training (PFMT) and bladder training (BT) and followed with surveys for 1 year. Content analysis of open-ended responses coded descriptions of approaches participants used to incorporate PFMT into daily life. Exploratory bivariate and logistic regression analyses determined predictors of approach used and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…However, their rate for daily PFM exercise (34.8%) were higher than that observed in our study. 41 As was the case during supervised intervention, long-term exercise rates did not differ between women who received the behavioral intervention alone or in combination with the continence pessary. Because PFM exercise generally declines over time, we might expect this trend to be greater for women using the continence pessary.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, their rate for daily PFM exercise (34.8%) were higher than that observed in our study. 41 As was the case during supervised intervention, long-term exercise rates did not differ between women who received the behavioral intervention alone or in combination with the continence pessary. Because PFM exercise generally declines over time, we might expect this trend to be greater for women using the continence pessary.…”
Section: Discussionmentioning
confidence: 75%
“…When patients link their exercises to such cues, the new exercise habit can be integrated with daily activities and PFM exercise becomes more automatic or habitual. For example, Hines and colleagues 41 found that women who performed their PFM exercises at routine times of the day had a 12-fold and 2.7-fold greater likelihood of achieving adherence during the initial 3 months of exercise and at the end of the first-year follow-up, respectively.…”
Section: Adherence To Behavioral Interventions For Stress Incontinencementioning
confidence: 99%
“…A few studies have examined factors that impact on women's participation in and adherence to a PFM training regimen during treatment (in class and at home), as well as in the long‐term, post‐treatment 27–29. In a qualitative descriptive study using individual and focus‐group interviews, In 2006, Milne and Moore27 studied the self‐care strategies employed by community‐dwelling individuals to adhere to the PFM training regimen at home.…”
Section: Types Of Behavior and Adherence Strategies For Effective Pfmmentioning
confidence: 99%
“…For example, the exercises could be scheduled before regular activities such as before meals. Scheduling PFMT at specific times is a more effective strategy than remembering to perform exercise on an ad hoc schedule (83). For optimal efficacy, PFMT may need to be continued for 8–12 weeks (35).…”
Section: Behavioural Interventionsmentioning
confidence: 99%